An Economic Equilibrium Model for Optimizing Passenger Transport Corridor Mode Structure Based on Travel Surplus - Wang, Xu; Song, Jingni; Wu, Qunqi (Sustainability, 2021)
Proper corridor configuration is the basic prerequisite for meeting demand to the maximum extent and optimally configuring transport resources. As the existing studies only pursue quantitative balance, without good understanding of the decision-making mechanism of passenger travel, they can hardly be used to guide effective infrastructure planning. The aim of this study was to put forward a new planning concept from the perspective of economics. Firstly, the decision-making mechanism of travel behavior was considered based on the demand subject, and the travel demand was classified. Next, the travel surplus of the demand subject was analyzed, and the travel decision-making criterion of maximizing the travel surplus was put forward. Then, a discrete economic equilibrium model for structural optimization of the passenger transport corridor was constructed and solved by the GlobalSearch algorithm. Finally, the effectiveness of the model and algorithm was verified through examples. The results indicate the good convergence of the algorithm. Different corridor travel demand, time value distribution and fixed cost of service mode all have great influence on the service mode configuration of the comprehensive transport passenger corridor and basically conform to the internal mechanism of supply and demand. The results show that the model and algorithm proposed in this paper are valid and can provide effective reference for the design and policy making of passenger transport corridor mode supply.